Lipids and insulin regulate mitochondrial‐derived peptide (MOTS‐c) in PCOS and healthy subjects - Ramanjaneya, Manjunath; Jerobin, Jayakumar; Bettahi, Ilham; Bensila, Milin; Aye, Myint; Siveen, Kodappully Sivaraman; Sathyapalan, Thozhukat; Skarulis, Monica; Abou‐Samra, Abdul‐Badi; Atkin, Stephen L. (Clinical endocrinology (Oxford), 2019)
Objective Polycystic ovarian syndrome (PCOS) is a heterogeneous endocrine disorder associated with mitochondrial dysfunction and insulin resistance (IR). MOTS‐c, a mitochondrial peptide, promotes insulin sensitivity (IS) through activating AKT and AMPK‐dependent pathways. The current study was designed to examine the response of MOTS‐c to lipids (intralipid) followed by insulin in PCOS and healthy subjects. Methods All subjects underwent 5‐hour intralipid/saline infusion with a hyperinsulinemic‐euglycaemic clamp in the final 2 hours. Plasma samples were collected to measure circulating MOTS‐c using a commercial ELISA kit. Subsequently, this was repeated following an eight‐week exercise intervention. Results Intralipid significantly increased plasma MOTS‐c both in controls and PCOS subjects, whilst the insulin infusion blunted the intralipid‐induced response seen for both lipids and MOT‐c. Intralipid elevated plasma MOTS‐c to 232 ± 124% of basal in control (P < 0.01) and to 349 ± 206% of basal in PCOS (P < 0.001) subjects. Administration of insulin suppressed intralipid‐induced MOTS‐c from 232 ± 124% to 165 ± 97% (NS) in control and from 349 ± 206% to 183 ± 177% (P < 0.05) in PCOS subjects, respectively. Following exercise, intralipid elevated plasma MOTS‐c to 305 ± 153% of basal in control (P < 0.01) and to 215 ± 103% of basal in PCOS (P < 0.01) subjects; insulin suppressed intralipid‐induced MOTS‐c only in controls. Conclusions In conclusion, this is the first study to show increased lipid enhanced circulating MOTS‐c whilst insulin attenuated the MOTS‐c response in human. Further, eight weeks of moderate exercise training did not show any changes in circulating MOTS‐c levels in healthy controls and in women with PCOS.